2008
DOI: 10.5713/ajas.2008.70252
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Reproductive Traits of Large White Pigs after Estrogen Receptor Gene-based Selection in Slovakia: Preliminary Results

Abstract: We investigated the effect of ESR gene-based selection on an improvement of litter size in the herds in real (nonexperimental) conditions. The pigs were selected for three years. In the tested population the pigs were mated according to a breeding scheme where the individuals with at least one ESR-B allele were preferred in the selection. In the control group (CP; n = 140) the pigs were mated just according to a breeding scheme without knowledge of the ESR genotype. We observed a significant increase in litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Nevertheless, the results of our study showed the possibility of PRLR utilization in marker-assisted selection (MAS) to increase litter size. The effects of the gene on litter size were more various and significant than in a case of the estrogen receptor gene in the same populations (Omelka et al, 2005;Omelka et al, 2006;Chvojková and Hraška, 2008). However, the number of analysed pigs was limited in our study.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, the results of our study showed the possibility of PRLR utilization in marker-assisted selection (MAS) to increase litter size. The effects of the gene on litter size were more various and significant than in a case of the estrogen receptor gene in the same populations (Omelka et al, 2005;Omelka et al, 2006;Chvojková and Hraška, 2008). However, the number of analysed pigs was limited in our study.…”
Section: Discussionmentioning
confidence: 69%
“…Berbagai pengujian berbasis genetik molekuler yang berasosiasi dengan genetik kuantitatif pada fenotipe tertentu memberikan peningkatan genetik yang signifikan. Sebagai contoh, pada babi betina, gen PRLR berhasil meningkatkan litter size dan litter size sapih (Omelka et al 2008;Rempel et al 2010) dan gen ESR mampu meningkatkan litter size (Chvojková & Hraška 2008). Pada babi jantan gen cluster of differentiation antigen 9 (CD9) dapat meningkatkan perkembangan spermatozoa dan penggunaan gen estrogen receptor 1 (ESR1) mampu meningkatkan aktivitas spermatogenesis dan perbaikan kualitas dan fertilitas spermatozoa (Gunawan et al 2011;Kaewmala et al 2011).…”
Section: Penerapan Bioteknologi Reproduksi Dan Genetika Molekuler Untunclassified